2000
DOI: 10.1021/bi001407j
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Parallax-Quench Method to Determine the Position of the Active-Site Loop of Cholesterol Oxidase in Lipid Bilayers

Abstract: To elucidate the cholesterol oxidase-membrane bilayer interaction, a cysteine was introduced into the active site lid at position-81 using the Brevibacterium enzyme. To eliminate the possibility of labeling native cysteine, the single cysteine in the wild-type enzyme was mutated to a serine without any change in activity. The loop-cysteine mutant was then labeled with acrylodan, an environment-sensitive fluorescence probe. The fluorescence increased and blue-shifted upon binding to lipid vesicles, consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Crystallographic studies suggest that cholesterol oxidase accesses substrate sterol molecules as they transiently project from the bilayer surface (27). The high activity of plasma membrane cholesterol above the threshold may reflect the frequency of such projections (18,26).…”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic studies suggest that cholesterol oxidase accesses substrate sterol molecules as they transiently project from the bilayer surface (27). The high activity of plasma membrane cholesterol above the threshold may reflect the frequency of such projections (18,26).…”
Section: Resultsmentioning
confidence: 99%
“…Polar head group species did not seem to exert a strong influence; in contrast, the RA values above threshold were orders of magnitude greater for unsaturated than saturated chains. The large differences in enzyme kinetics among the LUVs probably do not represent variations in K d , the disassociation constant for the binding of cholesterol oxidase, given that (a) the enzyme binds superficially to the surface of the vesicles; (b) the K d is rather insensitive to vesicle composition; and (c) the various phosphorylcholine phospholipids should bind the enzyme similarly yet had widely divergent RA values (38, 42, 43). …”
Section: Discussionmentioning
confidence: 99%
“…(62). ] Furthermore, the Michaelis, dissociation and catalytic constants (K m , K d and k cat ) of the enzyme should not vary with the cholesterol content of the bilayer (38, 39, 42, 43). We also considered whether the observed thresholds might reflect the limited solubility of the cholesterol, since sterols in excess of a sharp threshold form crystals in phospholipid bilayers (61).…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies have shown that this enzyme associates with the surface of the bilayer rather than penetrating into its nonpolar core. Projecting sterol molecules can just reach the catalytic cavity of the periphally-disposed enzyme [74,75]. The catalytic rate of cholesterol oxidase can therefore report on the constraints imposed by various phospholipids on the escape tendency (bobbing activity) of the sterols [57].…”
Section: Cholesterol Oxidase Susceptibility Of Membrane Cholesterolmentioning
confidence: 99%